2006
DOI: 10.1179/146532806x120363
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of fatal Rift Valley fever in a newborn

Abstract: Rift Valley Fever (RVF) is a viral disease transmitted to humans by mosquito bite and contact with animals or their infected tissues. Other modes of transmission include aerosol inhalation and possibly ingestion of raw milk from infected animals. We present a 5-day-old neonate with fatal RVF. Onset of the infant's illness on the 2nd day of life combined with positive RVF-IgM and serological evidence of maternal disease supports vertical transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 2 publications
3
49
0
Order By: Relevance
“…During the outbreak, a serious case of vertical transmission from mother to the baby was documented [41], similar to a previously reported case in Saudi Arabia in 2000 [42]. Many maternal deaths were observed in Central Sudan during the RVF outbreak [41], consistent with the claims recently made about the burden of emerging zoonotic infectious disease among women in general, and pregnant women in particular [43].…”
Section: Risk Factors For Severe Rvfv Infectionsupporting
confidence: 85%
“…During the outbreak, a serious case of vertical transmission from mother to the baby was documented [41], similar to a previously reported case in Saudi Arabia in 2000 [42]. Many maternal deaths were observed in Central Sudan during the RVF outbreak [41], consistent with the claims recently made about the burden of emerging zoonotic infectious disease among women in general, and pregnant women in particular [43].…”
Section: Risk Factors For Severe Rvfv Infectionsupporting
confidence: 85%
“…A previous case study from 2006 had suggested that RVFV can spread by vertical transmission from infected mothers to their unborn children [33]. During the recent 2007-2008 Sudanese outbreak, preterm labor due to acute RVF disease was also found to result in delivery of an anti-RVFV IgM positive baby with skin rash and hepatosplenomegaly, again suggesting that vertical transmission of RVFV probably does occur among humans [34].…”
Section: Human Rvf Diseasementioning
confidence: 99%
“…35 The virus has not shown direct human-to-human transmission, and there have been only a few documented cases of vertical transmission. 3638 …”
Section: Epidemiologymentioning
confidence: 99%
“…28,66,67 Even though isolated cases of vertical transmission have been documented, 3638 there appears to be no increase in apparent miscarriage in pregnant women. There is also no documented human-to-human transmission; infection of people appears to be limited to either mosquito bites or exposure to high titer animal tissues.…”
Section: Clinical Presentationmentioning
confidence: 99%